Association between napping and 24-hour blood pressure variability among university students: A pilot study - Dai, Jie; Wu, Hua-ying; Jiang, Xiao-dong; Tang, Yong-jie; Tang, Hao-Kai; Meng, Li; Huang, Na; Gao, Jing-yu; Li, Jian; Baker, Julien S.; Zheng, Chan-Juan; Yang, Yi-De (Frontiers in Pediatrics, 2023)
Background: Blood pressure variability (BPV) has been reported to be predictor of cardiovascular diseases and some cognitive diseases. However, the association between napping and BPV remains unknown. Materials and methods: A cross-sectional study including 105 university students was conducted. Participants’24-hour ambulatory blood pressure monitoring (24h ABPM) were measured, and napping behaviors were investigated. BPV were measured by the 24h ABPM, included standard deviation (SD), coefficient of variation (CV). Results: Among the participants, 61.9% reported daytime napping. We found that nap duration was significantly associated with daytime CV of diastolic blood pressure (DBP) (r=0.250, P=0.010), nighttime CV of systolic blood pressure (SBP) (r=0.217, P=0.026). Compared with the no napping group, 24h CV of DBP, daytime CV of DBP, 24h SD of DBP, and daytime SD of DBP are significantly higher in participants with napping duration ≥ 60min. With multivariable linear regression analysis, we found that nap duration was related with nighttime SD of SBP (β=1.052, 95% CI: 0.167-1.937, P=0.020) and daytime CV of DBP (β=0.785, 95% CI: 95% CI: 0.062-1.509, P=0.034). Conclusions: Napping duration are associated BPV among university students. Especially those with napping duration ≥ 60min had a significantly higher day CV of DBP than those non-nappers.